2016
DOI: 10.1176/appi.ps.201500461
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Needs of Homeless Youths With Mental Illness: Baseline Findings From a Housing First Trial

Abstract: This sample of homeless youths with mental illness had low education, high rates of substance use disorders and victimization, and problems accessing services. These findings suggest that youths have trajectories to homelessness and service needs that are distinct from adults and may guide future planning for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Based on earlier work, we know that our youngest participants had been homeless for years, with high rates of childhood trauma, chronic conditions like traumatic brain injury, and ongoing victimization, and therefore may take time after their housing is stabilized to recover in other areas and shift their use of acute medical services. 3 One exploratory outcome that did show some responsiveness to "Housing First" was satisfaction with leisure activities. This echoes the idea in Mullainathan and Shafir's Scarcity that great stress diminishes the ability to engage in other tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on earlier work, we know that our youngest participants had been homeless for years, with high rates of childhood trauma, chronic conditions like traumatic brain injury, and ongoing victimization, and therefore may take time after their housing is stabilized to recover in other areas and shift their use of acute medical services. 3 One exploratory outcome that did show some responsiveness to "Housing First" was satisfaction with leisure activities. This echoes the idea in Mullainathan and Shafir's Scarcity that great stress diminishes the ability to engage in other tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although including youth aged 16 to 17 years would have more accurately reflected existing services for homeless youth, differences in legal status for tenancy and, in some jurisdictions, informed consent make "Housing First" more complicated to study and implement in youth <18 years. These findings may not be generalizable to young people 7 CIS, Community Integration Scale psychological integration subscale with possible scores ranging from 4 to 20 (higher scores indicate higher level of integration); CSI, Colorado Symptom Index, a measure of psychiatric symptomatology with possible scores ranging from 5 to 70 (higher scores indicate more severe mental health symptoms); ED, emergency department; EQ-5D, EuroQoL5 Dimensions Visual Analog Scale, a measure of generic quality of life scored from 0 (worst imaginable health state) to 100 (best imaginable health state); GAIN-SPS, Global Assessment of Individual Needs Short Screener-Substance Problem Scale, a measure of substance use problems over the previous month, with possible scores ranging from 0 to 5 (higher scores indicate more symptoms of substance misuse); MCAS, Multnomah Community Ability Scale, a measure of community functioning with possible scores range from 17 to 85 (higher scores indicate a higher level of community functioning); QOLI-20, a measure of condition-specifi c quality of life with total possible scores ranging from 20 to 140 and subscale scores ranging as follows: family (4-28), fi nances (2-14), leisure (5-35), living situation (1-7), safety (4-28), social (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and overall quality of life (1-7), with higher scores indicating higher quality of life; RAS, Recovery Assessment Scale, a measure refl ecting various components of recovery with possible scores ranging from 22 to 110 (higher scores indicate higher degree of recovery); SF-12, Short Form 12 survey, a measure of physical and mental health status assessed by the physical component summary and mental health component summary, both of which range from 0 to 100 (higher scores indicate better health status). a Models included treatment group (reference: treatment as usual), time (month of visit; reference: baseline), study city (reference: Winnipeg), Aboriginal and ethnoracial status (reference: non-Aboriginal/non-ethnoracial), and treatment × time interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth experiencing homelessness also have numerous financial, structural, and personal barriers to accessing mental and emotional support (Christiani, Hudson, Nyamathi, Mutere, & Sweat, ; Hudson et al., ; Reid, Berman, & Forchuk, ), with up to 50% reporting a perceived unmet need for health care in the past 6 months (Kozloff et al., ). Homeless youth are also more likely to work in lower paying jobs without benefits or health insurance and have difficulties accessing affordable housing and education (National Health Care for the Homeless Council, ).…”
Section: Introductionmentioning
confidence: 99%
“…5; 6 Several recent studies have reported that homeless and precariously housed adults and youth have a high (53%-65% adult; 43% youth) lifetime prevalence of traumatic brain injury (TBI). [7][8][9][10] Unlike the general population, these homeless and precariously housed individuals most often sustain TBI through violent mechanisms such as assault. 11; 12 Moreover, homeless or precariously housed individuals who report a history of TBI are more likely to endorse a history of psychiatric diagnoses and substance abuse issues, 13; 14 lower physical and mental quality of life, 7; 8 seizures, 7; 15 and higher rates of emergency department and primary care physician use.…”
Section: Introductionmentioning
confidence: 99%